The Effect of Fadama II on Agro-Processing Among Farmers in Adamawa State, Nigeria - Madu, Umar Adamu; Phoa, John (Global Journal of Food and Agribusiness Management, 2022)
The study examined the effect of Fadama II project on agro-processing among the benefitting communities in Adamawa State, Nigeria. Two hundred respondents comprising of Fadama II project beneficiaries and non-project beneficiaries outside Fadama II communities that matched were randomly selected from five Local Government Areas each. Based on propensity score matching (PSM) and double difference estimator (DD), the data were analysed using simple statistical tool. To estimate the impact of the project, t-test analysis was used to determine the significant difference between the project participants and non-project participants. The results showed that the difference in quantity of processed products, price of processed products, amount realised from commercial processing and total income between the beneficiaries and non-beneficiaries were significant at p = 0.05. The paper recommends that much emphasis be laid on the importance agro-processing among the beneficiaries, the activities of the project be expanded to cover the whole state, other developmental project like food security project, ADP etc. should incorporate agro-processing into the mainstream of their activities as it has great potentials for poverty eradication.